Linking information provision to behavioural intentions: Moderating and mediating effects of message clarity and source credibility. Issue 1 (2nd December 2019) - Abunyewah, Matthew; Gajendran, Thayaparan; Maund, Kim; Okyere, Seth Asare
Abstract : Purpose: Disaster information is an important resource for flood preparedness, however, the transition of information provision to preparedness and consequently to damage reduction is complex. The nature of complexity has made it imperative to provide context-specific evidence on how disaster information provision influences intentions to prepare for flood hazard. This paper seeks to investigate how message clarity and source credibility mediate and moderate the relationship between information sufficiency and intentions to prepare. This paper aims to provide valuable insights into the relationship between the major components of disaster communication and their influence on intentions to prepare. Design/methodology/approach: The study used a cross-sectional survey design to test the relationship between information sufficiency, message clarity and source credibility. A total of 1, 064 questionnaire surveys were conducted on a face-to-face basis. The data collection was done in one month with ten research assistants. Participants of the study were randomly selected from adults over 18-years old who have lived in the study areas for at least three years. Responses from participants were analysed using a structural equation modelling (SEM) technique and SPSS AMOS version 24 software. Findings: Findings suggest that the information sufficiency-intentions to prepare relationship is enhanced when adequate disaster information communicated is clear and from a credible source. This implies that policymakers and risk communicators need to critically assess the clarity of disaster information content and the credibility of the source in the dissemination of information during the communication process. It also provides a better understanding of the factors that influence people's intentions to prepare for flood hazards. Research limitations/implications: This current study did not account for the specific nature or content of information necessary to increase message clarity and source credibility for disaster preparedness. In addition, the study did not cover the channels of communication ideal to stimulate people's intentions to flood preparedness. Although these do not undermine the significance of the present study, they present entry points for further studies. In view of the on-going urbanisation dynamics and the complex socio-spatial patterns emerging in the Greater Accra Area, it is recommended that further studies explore the channels of communication that will suit the diverse socio-spatial profile of residents (e.g. age, location, ethnicity, etc.). Originality/value: While a plethora of studies emphasize the role of source credibility, information sufficiency and message clarity towards disaster preparedness, there is at present little evidence on the mediating and moderating role of the communication variables. In this study, we propose and test the mediating and moderating role of message clarity and source credibility on the relationship between information sufficiency and intentions to prepare. The findings of this paper provide other incentives that encourage message audiences to take up precautionary measures towards flood hazards. In addition, with a view that people fail to prepare because of lack of sufficient information, the study findings suggest that the provision of sufficient information may enhance preparedness.